INTRODUCTION TO RESEARCH METHODOLOGY - Riak , Prof Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
This is an area where there is considerable disagreement on the definition of concepts, and what is right and wrong. Accordingly you should read widely and critically; never assume that you need to accept every concept and every assertion. You will probably be able to find an exception to every rule (see Feyerabend, 1975, for an extreme version of this principle). These notes are intended as a brief overview of the main issues. It is important that you read in more depth on the specific issues of particular concern to you. For example, if you intend to conduct some interviews or a questionnaire survey, it is important that you consult a suitable source of guidance on surveys, interviews and questionnaires – eg Saunders et al (2003), Robson (2002), Easterby-Smith et al (2002). I will use the word "method" for a specific research method such as a questionnaire survey. The word "methodology" refers to the study of methods in the same way as "psychology" is the study of the psyche. A research "strategy" is the overall approach to the project - which may include the use of several methods. The word "research" in this context covers everything that academic researchers do: the gathering of information about the world, the discovery and creation of theories and models to make sense of this information, reviewing and collating research done by others, as well as conceptual, mathematical and computational analysis.